Determinants of Customer Switching Intention: Empirical Evidence from Sharia Bank Mergers in Indonesia: Determinasi Beralihnya Nasabah: Fakta Empiris dari Merger Bank Syariah di Indonesia - Qurniawati, Rina; Nurohman, Yulfan; Fatharani, Aulia (Islamic Economics Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2022)
Abstract: This study examines the factors that affect customers switching intentions after three state-owned Indonesian sharia banks merge. Study on changing behavior in retail banks, especially in Islamic banks, is still rare. Especially in the context of mergers and acquisitions, this research is essential to do. The risk of losing customers in mergers and acquisitions (M&A) is very high because, during the integration phase, management often focuses on internal issues, leaving aside critical customer-related tasks. Therefore, a deeper understanding of the concept of M & A in the disciplines of marketing and consumer behavior is clearly needed to benefit academic knowledge and marketing practice. A total of one hundred and fifty respondents are selected using the quantitative method as sources of data collection. The questionnaires are distributed using a purposive sampling method in Surakarta, Indonesia. The software used for analysis is SEM-PLS. The results of this study state that inconvenience and religious motivation influence customer switching intentions. However, attitude and availability of suitable banks as a moderating variable did not influence customer switching intentions. This unsupport hypothesis is that the three Islamic banks merged are the banks under Badan Usaha Milik Negara (BUMN). When the merger occurs, Companies must increase marketing costs to retain existing customers. Future studies can explore the perceptions of bank employees to get their views on why customers consider switching banks when a merger occurs. Keywords: Mergers; Switching Intention; Inconvenience; Attitude; Religious Motivation. Abstrak: Penelitian ini mengkaji faktor-faktor yang mempengaruhi niat berpindahnya nasabah setelah tiga bank syariah milik pemerintah melakukan merger. Penelitian tentang perubahan perilaku di bank ritel, khususnya di bank syariah, masih jarang dilakukan. Khususnya dalam konteks merger dan akuisisi, maka penelitian ini penting dilakukan. Risiko kehilangan pelanggan dalam merger dan akuisisi sangat tinggi karena, selama fase integrasi, manajemen sering kali berfokus pada masalah internal, mengesampingkan tugas penting terkait pelanggan. Oleh karena itu, pemahaman yang lebih mendalam tentang konsep M&A dalam disiplin pemasaran dan perilaku konsumen jelas diperlukan untuk memberi manfaat bagi pengetahuan akademis dan praktik pemasaran. Ada seratus lima puluh responden dipilih dengan menggunakan metode kuantitatif sebagai sumber pengumpulan data. Kuesioner disebarkan dengan menggunakan metode purposive sampling di kota Surakarta, Indonesia. Perangkat lunak yang digunakan untuk analisis adalah SEM-PLS. Hasil penelitian ini menyatakan bahwa ketidaknyamanan dan motivasi keagamaan mempengaruhi niat berpindah pelanggan. Namun, sikap dan ketersediaan bank yang sesuai sebagai variabel moderasi tidak mempengaruhi niat berpindahnya nasabah. Temuan ini tidak sesuai dengan hipotesis yang mana ketiga bank syariah yang merger adalah bank-bank yang tergabung dalam Badan Usaha Milik Negara. Ketika merger terjadi, Perusahaan harus meningkatkan biaya pemasaran untuk mempertahankan pelanggan yang sudah ada. Penelitian ke depan dapat mengeksplorasi persepsi karyawan bank untuk mendapatkan pandangan mereka tentang mengapa pelanggan mempertimbangkan untuk beralih bank ketika terjadi merger. Kata Kunci: Merger; Beralih Niat; Ketidaknyamanan; Sikap; Motivasi Keagamaan.